2010
DOI: 10.1002/jrs.2662
|View full text |Cite
|
Sign up to set email alerts
|

CARS thermometry revisited in lightof the intramolecular perturbation

Abstract: The rigid rotor approximation (RRA) is commonly assumed in the Raman cross section used in thermometric analysis based on coherent anti-Stokes Raman scattering (CARS). In this paper, we discuss instead the role of the coupling between molecular vibrations and rotations in view of the alterations found in the amplitude of CARS signals of basic molecules and, in the end, we demonstrate that the deviation of a few percent from the RRA results in corrections to the measured temperature that are comparable to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 28 publications
(51 reference statements)
2
26
0
Order By: Relevance
“…The rigid rotor approximation is commonly assumed in the Raman cross section used in thermometric analysis based on CARS. To address this assumption, Marrocco discussed instead the role of the coupling between molecular vibrations and rotations in view of the alterations found in the amplitude of CARS signals of basic molecules . A cluster of point sources can generate optical radiation in a manner substantially different from what characterizes the emission of a single point source.…”
Section: Nonlinear and Related Time‐resolved Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The rigid rotor approximation is commonly assumed in the Raman cross section used in thermometric analysis based on CARS. To address this assumption, Marrocco discussed instead the role of the coupling between molecular vibrations and rotations in view of the alterations found in the amplitude of CARS signals of basic molecules . A cluster of point sources can generate optical radiation in a manner substantially different from what characterizes the emission of a single point source.…”
Section: Nonlinear and Related Time‐resolved Raman Spectroscopymentioning
confidence: 99%
“…To address this assumption, Marrocco discussed instead the role of the coupling between molecular vibrations and rotations in view of the alterations found in the amplitude of CARS signals of basic molecules. [89] A cluster of point sources can generate optical radiation in a manner substantially different from what characterizes the emission of a single point source. A paper by Nichelatti explores this subject in view of its applications to coherent scattering that is typical of nonlinear Raman processes.…”
Section: Coherent Anti-stokes Raman Spectroscopymentioning
confidence: 99%
“…The Herman-Wallis factor given by Tipping and Bouanich [33] is considered to be accurate, and it is widely used in the literature [34][35][36][37]. We also find comparisons [38,39] between this form of the Herman-Wallis factor and those given by Buldakov et al [26], as if they have separate origins.…”
Section: Raman Simulationmentioning
confidence: 84%
“…Marrocco studied the limitations of this approach and found that for small molecules such as hydrogen, inaccuracies of the order of 10% in the line intensity are observed while larger molecules like nitrogen showed smaller deviations . He compared the effects on vibrational CARS thermometry of nitrogen with a rigid rotor approximation, which neglects ro‐vibrational coupling, and found deviations of a few percent . In vibrational CARS of oxygen the systematic errors especially at high temperature led to the conclusion that advanced models of the Herman–Wallis factor are required in order to ensure accurate temperature measurements .…”
Section: Applications To Gas‐phase and Combustion Systemsmentioning
confidence: 99%